2017
DOI: 10.1186/s11671-017-2263-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects in Assembly of Magnetic Nanoparticles

Abstract: A specific absorption rate of a dilute assembly of various random clusters of iron oxide nanoparticles in alternating magnetic field has been calculated using Landau–Lifshitz stochastic equation. This approach simultaneously takes into account both the presence of thermal fluctuations of the nanoparticle magnetic moments and magneto-dipole interaction between the nanoparticles of the clusters. It is shown that for usual 3D clusters, the intensity of the magneto-dipole interaction is determined mainly by the cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 42 publications
6
93
0
Order By: Relevance
“…6 shows, for all cases considered there is an optimal diameter of the nanoparticles corresponding to the maximal SAR value. In addition, in accordance with the results obtained previously [6] for fractal clusters of PC type with relatively small number of magnetic nanoparticles, N = 90, the maximal SAR value increases as a function of the non magnetic shell thickness L .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…6 shows, for all cases considered there is an optimal diameter of the nanoparticles corresponding to the maximal SAR value. In addition, in accordance with the results obtained previously [6] for fractal clusters of PC type with relatively small number of magnetic nanoparticles, N = 90, the maximal SAR value increases as a function of the non magnetic shell thickness L .…”
Section: Resultssupporting
confidence: 91%
“…One of the reasons of such behavior is the property of magnetic particles to agglomerate [4] and to form fractal-like structures [5] at in-vivo conditions. As a result, SAR of an assembly of magnetic nanoparticles distributed in tissue decreases considerably under the influence of strong magneto-dipole interactions between the nanoparticles of the cluster [4,6]. It is well known [7] that two different types of fractal clusters can be constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Dashed lines are from the analytical model given by Eqs. (28) and (39). Dotted line is the Langevin function [Eq.…”
Section: A Magnetically Isotropic Particles In a Bulk Solid Matrixmentioning
confidence: 99%
“…For simplicity, it is sometimes assumed that microspheres and nanoclusters contain non-interacting and magnetically isotropic single-domain particles 7,[20][21][22] . However, in recent years quasi-spherical rigid clusters of different sizes have been actively studied via numerical simulations 11,[23][24][25][26][27][28] . And it has been repeatedly demonstrated that interactions between embedded particles as well as their magnetic anisotropy can have a noticeable impact on the cluster static 11,[23][24][25] and dynamic [25][26][27][28] magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulations are performed by solving stochastic Landau-Lifshitz (LL) equation [7][8][9]. This approach takes into account both thermal fluctuations of the particle magnetic moments and strong magnetodipole interaction [10][11] in assemblies of dense fractal-like aggregates of nanoparticles. It has been discovered recently [12] that fractal clusters of nanoparticles originate in biological cells loaded with magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%